Why India's food and agricultural systems hold the key to climate action - Saha, Ankit; Singh, Vartika; Kumar Ghosh, Ranjan (FABLE Consortium, 2026)
The FABLE India team invited policymakers, researchers, and students to step into India’s food and climate future through a FABLE “Serious Game” and expert panels. Participants explored the complex trade-offs in agriculture, discovering how coordinated action, crop diversity, and farmer empowerment can turn challenges into low-emission solutions that also strengthen food security.